The Role of Computed Tomography Angiography in Patients Undergoing Evaluation for Minimally Invasive Cardiac Surgery. Issue 1 (January 2015) - Youssef, Samuel J.; Millan, Juan A.; Youssef, Gabriel M.; Earnheart, Amanda; Lehr, Eric J.; Barnhart, Glenn R.
<x xml:space="preserve">Abstract</x> Objective An increasing number of patients are undergoing surgical procedures using minimally invasive cardiac surgery (MICS). These techniques use conventional or retrograde arterial perfusion with direct aortic cross-clamping or endoballoon occlusion. Precise knowledge of the arterial tree is required to avoid complications and to plan for the operation. We examined the role of computed tomography angiography (CTA) in evaluating patients for MICS. Methods We reviewed all consecutive candidates undergoing CTA during preoperative evaluation for MICS aortic, mitral, tricuspid, Maze, atrial septal defect, or myxoma procedures between February 2008 and May 2010. The CTA findings of patients excluded from MICS were compared against those successfully undergoing MICS. Results One hundred eleven MICS candidates underwent preoperative CTA. Thirty-five (32%) had single or multiple CTA findings precluding MICS and underwent sternotomy. Seventy-six (68%) had favorable CTA findings and underwent MICS. The MICS group had a mean age of 62 years, with 29 women (39%); the non-MICS group had a mean age of 68 years, with 17 women (48%). Of the patients excluded from MICS, two (6%) had diminished or absent lower extremity pulses. All MICS patients (except for aortic) had successful use of the endoballoon. There were no perfusion or peripheral vascular complications. There was one stroke, one lymphocele, and one death (chronic obstructive pulmonary disease exacerbation). Conclusions Computed tomography angiography is of fundamental importance in evaluating patients for MICS. It can identify calcified regions that make for threatening catheter passage with subsequent retrograde arterial perfusion. Abnormalities of the arterial tree are identified. The use of CTA-guided patient selection can thus avoid major perioperative complications.